Hepatic artery stenosis after liver transplantation: Is endovascular treatment always necessary?. Issue 2 (February 2015) - Pulitano, Carlo; Joseph, David; Sandroussi, Charbel; Verran, Deborah; Strasser, Simone I.; Shackel, Nicholas A.; McCaughan, Geoffrey W.; Crawford, Michael
<x xml:space="preserve">Abstract</x> Hepatic artery stenosis (HAS) is thought to predispose patients to biliary complications secondary to ischemic injury. Despite this, the clinical significance of HAS remains poorly defined. The aims of this study were to determine the prevalence and outcomes of HAS and to define which patients might benefit from endovascular treatment. From a prospective database of 662 adult patients undergoing liver transplantation between 2000 and 2011, we identified 54 patients who developed HAS. HAS was defined as any stenosis > 70% that was seen during multidetector computed tomographic angiography (MDCTA) or digital subtraction angiography. The benefit of endovascular therapy was evaluated with propensity score matching. New biliary complications occurred in 17 patients (31.4%), and 23 of the 54 study patients with HAS received endovascular treatment. Among the propensity score–matched patients, the biliary stricture–free survival time was significantly longer for those who received endovascular therapy (P = 0.03). An incidental diagnosis (P = 0.07) and a time from transplantation > 6 months (P = 0.021) were associated with a reduced risk of developing biliary stricture. Patients with symptomatic HAS who received treatment had better biliary stricture–free survival than patients who were treated conservatively, although no significant difference was recorded (P = 0.11). No patient with asymptomatic HAS and normal liver function tests developed biliary strictures. In conclusion, HAS intervention was associated with improved biliary stricture–free survival. In patients with late‐onset HAS (≥6 months) and asymptomatic patients, endovascular treatment is not warranted. Liver Transpl 21:162‐168, 2015. © 2014 AASLD.